JunD Regulates Pancreatic β-Cells Function by Altering Lipid Accumulation - Wang, Kexin; Cui, Yixin; Lin, Peng; Yao, Zhina; Sun, Yu (Frontiers in Endocrinology, 2021)
The impairment of pancreatic β-cells function is partly caused by lipotoxicity, which aggravates the development of type 2 diabetes mellitus. Activator Protein 1 member JunD modulates apoptosis and oxidative stress. Recently, it has been found that JunD regulates lipid metabolism in hepatocytes and cardiomyocytes. Here, we studied the role of JunD in pancreatic β-cells. The lipotoxic effects of palmitic acid on INS-1 cells were measured, and JunD small-interfering RNA was used to assess the effect of JunD in regulating lipid metabolism and insulin secretion. The results showed that PA stimulation induced the overexpression of JunD, impaired glucose-stimulated insulin secretion, and increased intracellular lipid accumulation of β-cells. Moreover, the genes expression involved in lipid metabolism (SCD1, Fabp4, Fas, Cd36, Lpl, and Plin5) was upregulated, while genes expression involved in the pancreatic β-cells function (such as PDX1, NKX6.1, GLUT2, and IRS-2) was decreased. Gene silencing of JunD reversed the lipotoxic effects induced by PA on β-cells. These results suggested that JunD regulated the function of pancreatic β-cells by altering lipid accumulation.